A high-toughness wear-resistant cable and preparation method thereof
By generating zirconia particles on the surface of carbon nanotubes and grafting with coupling agent, and combining modified ABS and maleic anhydride grafted polypropylene, the problem of insufficient wear resistance and bending resistance of cable materials is solved, and the mechanical properties and wear resistance of the material are significantly improved.
Patent Information
- Application Number
- CN202411393649.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-30
AI Technical Summary
When existing cable materials face oil stains, chemicals and mechanical wear, they lack wear and bending resistance, resulting in rapid wear and structural instability of the outer shell.
By generating uniformly distributed zirconia particles on the surface of the carbon nanotubes and grafting them with coupling agents, they can form organic copolymers with eugenol and glycidyl methacrylate. The modified ABS is connected to the carboxy group through oleic acid, and grafting polypropylene as a compatible agent with maleic anhydride, thereby increasing the binding force of polypropylene and ABS.
The mechanical properties and wear resistance of polypropylene materials are significantly improved, ensuring that the cable can maintain structural integrity and electrical performance stability under extreme conditions.
Smart Images

Figure BDA0005073132170000021 
Figure BDA0005073132170000051 
Figure BDA0005073132170000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable materials and relates to a high-toughness wear-resistant cable and a preparation method thereof. Background Art
[0002] In actual applications, cables may come into contact with a variety of oils, chemicals, and be subjected to mechanical wear, so they must have excellent wear and bending resistance. The purpose of ensuring wear resistance is to prevent the cable sheath from being quickly worn out due to frequent friction, thereby effectively avoiding the exposure of the internal conductor and the possible risk of short circuit. The strengthening of bending resistance ensures that the cable can maintain its structural integrity and electrical performance stability even under extreme bending conditions, which is of immeasurable importance for maintaining the continuous operation and safety of the automation system.
[0003] The outer layer of the cable is generally made of polypropylene, which is a cheap, lightweight, non-toxic general-purpose plastic. It has the disadvantages of being brittle at low temperatures, low mechanical strength and hardness, large molding shrinkage, poor toughness, poor wear resistance, easy aging and poor heat resistance.
[0004] As a unique nano inorganic material, carbon nanotubes have a unique structure and physical properties that give them a series of excellent properties. Due to their unique arrangement of carbon atoms, carbon nanotubes can evenly disperse stress when subjected to external forces, thereby avoiding fracture caused by local stress concentration. This high strength property enables carbon nanotubes to maintain structural integrity when subjected to wear, thus showing excellent wear resistance. However, the compatibility between carbon nanotubes and polypropylene is poor, and the interface between the two is often not tight enough, resulting in a decrease in the overall performance of the composite material.
[0005] Styrene-butadiene-acrylonitrile, referred to as ABS, has excellent comprehensive properties and is a good toughening modifier. However, the -CN polar group carried by the acrylonitrile phase in ABS leads to poor compatibility with PP. In addition, the solubility parameters of PP and ABS are quite different. From a structural point of view, PP is crystalline, non-polar, and random, and is also incompatible with polar ABS. Summary of the invention
[0006] The purpose of the present invention is to provide a high-toughness wear-resistant cable and a preparation method thereof. The present invention generates uniformly distributed zirconium oxide particles on the surface of carbon nanotubes and grafts them with a coupling agent so that they can form an organic copolymer with eugenol and glycidyl methacrylate. The modified ABS is connected to a carboxyl group through oleic acid, and maleic anhydride grafted polypropylene is used as a compatibilizer to improve the bonding force between polypropylene and ABS, thereby improving the mechanical properties and wear resistance of the polypropylene material.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0009]
[0010] As a preferred technical solution of the present invention, the cable body includes a conductive core and a metal shielding layer, and the metal shielding layer and the protective layer are filled with elastic resin.
[0011] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of an antioxidant, a lubricant and an ultraviolet absorber in a mass ratio of 2.0-2.5:3.0-3.8:1.8-2.2.
[0012] As a preferred technical solution of the present invention, the lubricant is one or both of oxidized polyethylene wax and montan wax; the antioxidant is one or more of antioxidant 1010, antioxidant 1098, antioxidant 168 and antioxidant 1076; and the ultraviolet absorber is one or both of UV-9 and BP-6.
[0013] As a preferred technical solution of the present invention, the preparation method of the modified ABS comprises the following steps:
[0014] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder for melt extrusion, and granulated to obtain modified ABS; the temperature of the melt extrusion is 170-180°C; the mass ratio of the ABS, the reaction monomer and the initiator is 14-16:1.5-1.8:0.10-0.12; the reaction monomer is prepared by mixing a carboxylic acid monomer and styrene in a mass ratio of 4-5:1.0-1.3; the carboxylic acid monomer is oleic acid; and the initiator is initiator DCP.
[0015] As a preferred technical solution of the present invention, the preparation method of the modified composite filler comprises the following steps:
[0016] Step 1: After mixing zirconium oxychloride octahydrate and anhydrous ethanol, add pretreated carbon nanotubes for ultrasonic treatment, adjust the pH value, place in a reaction kettle for heat preservation, perform vacuum filtration, dry and calcine to obtain composite particles;
[0017] Step 2: heating and stirring the composite particles, anhydrous ethanol and coupling agent, filtering out the filtrate, washing, and drying to obtain a preform;
[0018] Step 3: Mix the preform, anhydrous ethanol, mixed monomers and initiator, stir at a constant temperature, filter out the filtrate, wash, and dry to obtain a modified composite filler.
[0019] As a preferred technical solution of the present invention, in the embodiments and comparative examples of the present invention, the preparation method of the pretreated carbon nanotubes includes the following steps: heating the carbon nanotubes and the acidic solution to 100°C under magnetic stirring, condensing and refluxing for 6 hours, filtering the solids, washing with ionized water until the filtrate is neutral, and vacuum drying at 70°C for 24 hours to obtain the acidified carbon nanotubes; wherein the dosage ratio of the acidic solution to the carbon nanotubes is 30:1g; and the volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is 1:3.
[0020] As a preferred technical solution of the present invention, in step one, the stirring and mixing is stirring at a speed of 400-600r / min for 20-30min; the ultrasonic treatment is ultrasonication at a frequency of 300-400W for 10-20min; the heat preservation treatment is heat preservation at 120-150°C for 10-16h; the pH value is adjusted to 10-12 using sodium hydroxide; the drying is drying at 80°C to constant weight; the calcination is calcining at 500-560°C in an argon atmosphere for 1-2h; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2-3:90-100:8-10.
[0021] As a preferred technical solution of the present invention, in step 2, the heating and stirring is stirring at a temperature of 60-70°C for 4-5h; the washing is washing three times with anhydrous ethanol; the drying is drying at a temperature of 80°C to constant weight; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 14-16:40-50:6.0-7.2; and the coupling agent is vinyltrimethoxysilane.
[0022] As a preferred technical solution of the present invention, in step three, the constant temperature stirring is constant temperature stirring at 70-75°C for 6-7h; the washing is washing three times with anhydrous ethanol; the drying is drying to constant weight at 80°C; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.0-3.6:1.0-1.3; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 24-26:80-90:8.0-9.4:0.18-0.22; and the initiator is azobisisobutyronitrile.
[0023] The invention discloses a method for preparing a high-toughness wear-resistant cable. The method comprises the following steps: weighing polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent by weight, kneading them at 150-160°C for 20-30 minutes, placing them in a twin-screw extruder, melting and extruding them at 180-200°C, and wrapping them on the outer wall of the cable body.
[0024] Beneficial effects of the present invention:
[0025] The invention generates uniformly distributed zirconium oxide particles on the surface of carbon nanotubes and grafts them with a coupling agent so that they can form an organic copolymer with eugenol and glycidyl methacrylate, and the modified ABS is connected with a carboxyl group through oleic acid, and maleic anhydride grafted polypropylene is combined as a compatibilizer to improve the bonding force between polypropylene and ABS, thereby improving the mechanical properties and wear resistance of the polypropylene material. DETAILED DESCRIPTION
[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0027] Example 1
[0028] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0029]
[0030] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of antioxidant 1010, oxidized polyethylene wax and ultraviolet absorber UV-9 in a mass ratio of 2.0:3.0:1.8.
[0031] The preparation method of the modified ABS comprises the following steps:
[0032] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder and melt-extruded at a temperature of 170° C., and then granulated to obtain modified ABS; the mass ratio of the ABS, the reaction monomer and the initiator is 14:1.5:0.10; the reaction monomer is a mixture of oleic acid and styrene in a mass ratio of 4:1.0; and the initiator is initiator DCP.
[0033] The preparation method of the modified composite filler comprises the following steps:
[0034] Step 1: After stirring zirconium oxychloride octahydrate and anhydrous ethanol at a speed of 400 r / min for 20 minutes, pretreated carbon nanotubes are added and ultrasonicated at a frequency of 300 W for 10 minutes, the pH value is adjusted to 10 with sodium hydroxide, and the mixture is placed in a reactor and kept at 120° C. for 10 hours, and then vacuum filtered, dried at 80° C. to constant weight, and calcined at 500° C. in an argon atmosphere for 2 hours to obtain composite particles; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2:90:8;
[0035] Step 2: Stir the composite particles, anhydrous ethanol and coupling agent at 60° C. for 4 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry at 80° C. to constant weight to obtain a preform; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 14:40:6.0; the coupling agent is vinyltrimethoxysilane;
[0036] Step 3: After mixing the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature of 70°C for 6 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry to constant weight at 80°C to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.0:1.0; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 24:80:8.0:0.18; the initiator is azobisisobutyronitrile.
[0037] A preparation method of a high-toughness wear-resistant cable comprises the following steps: polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent are weighed by weight and kneaded at 150°C for 20 minutes, placed in a twin-screw extruder and melt-extruded at 180°C to obtain a protective layer, and the molten protective layer material is wrapped on the outer wall of the cable body to obtain a high-toughness wear-resistant cable.
[0038] Example 2
[0039] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0040]
[0041] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of antioxidant 1010, oxidized polyethylene wax and ultraviolet absorber UV-9 in a mass ratio of 2.1:3.2:1.9.
[0042] The preparation method of the modified ABS comprises the following steps:
[0043] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder and melt-extruded at a temperature of 170° C., and then granulated to obtain modified ABS; the mass ratio of the ABS, the reaction monomer and the initiator is 14.5:1.58:0.11; the reaction monomer is a mixture of oleic acid and styrene in a mass ratio of 4.2:1.1; and the initiator is initiator DCP.
[0044] The preparation method of the modified composite filler comprises the following steps:
[0045] Step 1: After stirring zirconium oxychloride octahydrate and anhydrous ethanol at a speed of 450 r / min for 25 minutes, pretreated carbon nanotubes are added and ultrasonicated at a frequency of 325 W for 12 minutes, the pH value is adjusted to 11 with sodium hydroxide, and the mixture is placed in a reactor and kept at 128° C. for 12 hours, and then vacuum filtered, dried at 80° C. to constant weight, and calcined at 515° C. in an argon atmosphere for 1.2 hours to obtain composite particles; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2.2:92:8.5;
[0046] Step 2: Stir the composite particles, anhydrous ethanol and coupling agent at 62° C. for 4.2 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry at 80° C. to constant weight to obtain a preform; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 14.5:42:6.3; the coupling agent is vinyltrimethoxysilane;
[0047] Step 3: After mixing the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature of 70°C for 6.5 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry to constant weight at 80°C to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.2:1.1; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 24.5:82:8.4:0.19; the initiator is azobisisobutyronitrile.
[0048] A preparation method of a high-toughness wear-resistant cable comprises the following steps: polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent are weighed by weight, mixed at 152°C for 22 minutes, placed in a twin-screw extruder for melt extrusion at 185°C to obtain a protective layer, and the molten protective layer material is wrapped on the outer wall of the cable body to obtain a high-toughness wear-resistant cable.
[0049] Example 3
[0050] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0051]
[0052]
[0053] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of antioxidant 1010, oxidized polyethylene wax and ultraviolet absorber UV-9 in a mass ratio of 2.2:3.4:2.
[0054] The preparation method of the modified ABS comprises the following steps:
[0055] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder and melt-extruded at a temperature of 175° C., and then granulated to obtain modified ABS; the mass ratio of the ABS, the reaction monomer and the initiator is 15:1.65:0.11; the reaction monomer is a mixture of oleic acid and styrene in a mass ratio of 4.5:1.15; and the initiator is initiator DCP.
[0056] The preparation method of the modified composite filler comprises the following steps:
[0057] Step 1: After stirring zirconium oxychloride octahydrate and anhydrous ethanol at a speed of 500 r / min for 25 minutes, pretreated carbon nanotubes are added and ultrasonicated at a frequency of 350 W for 15 minutes, the pH value is adjusted to 11 with sodium hydroxide, and the mixture is placed in a reactor and kept at 135° C. for 13 hours, and then vacuum filtered, dried at 80° C. to constant weight, and calcined at 530° C. in an argon atmosphere for 1.5 hours to obtain composite particles; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2.5:95:9;
[0058] Step 2: Stir the composite particles, anhydrous ethanol and coupling agent at 65° C. for 4.5 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry at 80° C. to constant weight to obtain a preform; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 15:45:6.6; the coupling agent is vinyltrimethoxysilane;
[0059] Step 3: After mixing the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature of 72°C for 6.5 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry to constant weight at 80°C to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.3:1.15; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 25:85:8.7:0.2; the initiator is azobisisobutyronitrile.
[0060] A preparation method of a high-toughness wear-resistant cable comprises the following steps: polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent are weighed by weight and kneaded at 155°C for 25 minutes, placed in a twin-screw extruder and melt-extruded at 190°C to obtain a protective layer, and the molten protective layer material is wrapped on the outer wall of the cable body to obtain a high-toughness wear-resistant cable.
[0061] Example 4
[0062] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0063]
[0064] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of antioxidant 1010, oxidized polyethylene wax and ultraviolet absorber UV-9 in a mass ratio of 2.4:3.6:2.1.
[0065] The preparation method of the modified ABS comprises the following steps:
[0066] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder and melt-extruded at a temperature of 178° C., and then granulated to obtain modified ABS; the mass ratio of the ABS, the reaction monomer and the initiator is 15.5:1.7:0.11; the reaction monomer is a mixture of oleic acid and styrene in a mass ratio of 4.8:1.23; and the initiator is initiator DCP.
[0067] The preparation method of the modified composite filler comprises the following steps:
[0068] Step 1: After stirring zirconium oxychloride octahydrate and anhydrous ethanol at a speed of 550 r / min for 28 minutes, pretreated carbon nanotubes are added and ultrasonicated at a frequency of 375 W for 18 minutes, and the pH value is adjusted to 11.5 with sodium hydroxide, and the mixture is placed in a reactor and kept at 140° C. for 14 hours, and then vacuum filtered, dried at 80° C. to constant weight, and calcined at 540° C. in an argon atmosphere for 1.8 hours to obtain composite particles; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2.8:98:9.5;
[0069] Step 2: Stir the composite particles, anhydrous ethanol and coupling agent at 68° C. for 4.8 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry at 80° C. to constant weight to obtain a preform; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 15.5:48:6.9; the coupling agent is vinyltrimethoxysilane;
[0070] Step 3: After mixing the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature of 74°C for 6.8 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry to constant weight at 80°C to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.4:1.23; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 25.5:88:9:0.21; the initiator is azobisisobutyronitrile.
[0071] A preparation method of a high-toughness wear-resistant cable comprises the following steps: polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent are weighed by weight, kneaded at 158°C for 28 minutes, placed in a twin-screw extruder for melt extrusion at 195°C to obtain a protective layer, and the molten protective layer material is wrapped on the outer wall of the cable body to obtain a high-toughness wear-resistant cable.
[0072] Example 5
[0073] A high-toughness wear-resistant cable, comprising a cable body and a protective layer arranged on the outer wall of the cable body, wherein the protective layer comprises the following components in parts by weight:
[0074]
[0075] The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of antioxidant 1010, oxidized polyethylene wax and ultraviolet absorber UV-9 in a mass ratio of 2.5:3.8:2.2.
[0076] The preparation method of the modified ABS comprises the following steps:
[0077] ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder and melt-extruded at a temperature of 180° C., and then granulated to obtain modified ABS; the mass ratio of the ABS, the reaction monomer and the initiator is 16:1.8:0.12; the reaction monomer is a mixture of oleic acid and styrene in a mass ratio of 5:1.3; and the initiator is initiator DCP.
[0078] The preparation method of the modified composite filler comprises the following steps:
[0079] Step 1: After stirring zirconium oxychloride octahydrate and anhydrous ethanol at a speed of 600 r / min for 30 minutes, pretreated carbon nanotubes are added and ultrasonicated at a frequency of 400 W for 20 minutes, the pH value is adjusted to 12 with sodium hydroxide, and the mixture is placed in a reactor and kept at 150° C. for 16 hours, and then vacuum filtered, dried at 80° C. to constant weight, and calcined at 560° C. in an argon atmosphere for 1 hour to obtain composite particles; the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 3:100:10;
[0080] Step 2: Stir the composite particles, anhydrous ethanol and coupling agent at 70°C for 5 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry at 80°C to constant weight to obtain a preform; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 16:50:7.2; the coupling agent is vinyltrimethoxysilane;
[0081] Step 3: After mixing the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature of 75°C for 7 hours, filter out the filtrate, wash three times with anhydrous ethanol, and dry to constant weight at 80°C to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.6:1.3; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 26:90:9.4:0.22; the initiator is azobisisobutyronitrile.
[0082] A preparation method of a high-toughness wear-resistant cable comprises the following steps: polypropylene, modified ABS, a compatibilizer, a modified composite filler and an auxiliary agent are weighed by weight and kneaded at 160°C for 30 minutes, placed in a twin-screw extruder and melt-extruded at 200°C to obtain a protective layer, and the molten protective layer material is wrapped on the outer wall of the cable body to obtain a high-toughness wear-resistant cable.
[0083] Comparative Example 1
[0084] Compared with Example 4, Comparative Example 1 is different in that oleic acid is not used, and the other components, preparation steps and parameters are the same.
[0085] Comparative Example 2
[0086] Compared with Example 4, Comparative Example 2 is different in that pretreated carbon nanotubes replace composite particles, and the other components, preparation steps and parameters are the same.
[0087] Comparative Example 3
[0088] Compared with Example 4, Comparative Example 3 is different in that zirconium dioxide replaces the composite particles, and the other components, preparation steps and parameters are the same.
[0089] Comparative Example 4
[0090] Compared with Example 4, the difference of Comparative Example 4 is that no coupling agent is used in step 2, and the other components, preparation steps and parameters are the same.
[0091] Comparative Example 5
[0092] Compared with Example 4, the difference in Comparative Example 5 is that eugenol is not used in step 3, and the other components, preparation steps and parameters are the same.
[0093] Comparative Example 6
[0094] Compared with Example 4, Comparative Example 6 is different in that glycidyl methacrylate is not used in step 3, and the remaining components, preparation steps and parameters are the same.
[0095] The protective layers prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to the following tests, respectively. The test results are shown in Table 1.
[0096] Mechanical properties test: tensile strength and elongation at break tested according to GB / T 2951.11-2008;
[0097] Wear resistance test: A sample of 3cm×2cm×0.5cm was prepared and the wear resistance test was carried out using a friction and wear testing machine; the dual sample was steel 440-C, the rotation speed was 400r / min, the load was 100N, the experimental time was 1h, and the wear amount was measured by the weighing method.
[0098] Table 1
[0099] Tensile strength(MPa) Elongation at break (%) Wear amount (mg) Example 1 33.3 357 93 Example 2 33.2 361 95 Example 3 32.8 355 97 Example 4 33.5 362 90 Example 5 32.9 366 98 Comparative Example 1 25.2 294 164 Comparative Example 2 20.3 260 191 Comparative Example 3 19.4 249 199 Comparative Example 4 23.1 274 176 Comparative Example 5 25.3 302 161 Comparative Example 6 24.7 286 169
[0100] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the protective layer of the high-toughness wear-resistant cable prepared in Examples 1-5 of the present invention has excellent tensile strength and elongation at break, and has better wear resistance. By comparing Examples 1-5 with Comparative Examples 1-6, combined with the analysis of Table 1, it can be seen that the present invention uses anhydrous ethanol as a dispersing agent, and the zirconium oxide particles generated by the reaction are more evenly distributed on the surface of the carbon nanotubes, thereby improving the dispersibility of the carbon nanotubes, increasing the hydroxyl groups on the surface of the composite particles, and improving the grafting effect between the composite particles and the coupling agent. The introduced carbon-carbon double bonds can form organic copolymers with eugenol and glycidyl methacrylate to form an organically modified coating on the composite particles, thereby increasing their compatibility in the system. By compounding carbon nanotubes and zirconium oxide, the mechanical properties and wear resistance of the polypropylene material are increased, and the modified ABS is connected to the carboxyl group through oleic acid, and the length of oleic acid is increased. The carbon chain can give the polypropylene material excellent flexibility. The connected carboxyl group can improve the binding force of ABS in the system through the interaction with metal zirconium. At the same time, the carboxyl group can also react with the epoxy group on the modified composite filler to improve the toughness and wear resistance of the polypropylene material. The hydroxyl and methoxy groups of the eugenol combined with the modified composite filler can produce hydrogen bonds with the nitrile group of acrylonitrile, so that the maleic anhydride grafted polypropylene compatibilizer is mainly used, and the modified composite filler is used as a compatibilizer to improve the binding force of polypropylene and ABS, while also reducing the particle size and distribution of the dispersed phase. The benzene ring structure on ABS and eugenol can improve the mechanical properties and wear resistance of the polypropylene material.
[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-toughness wear-resistant cable, characterized in that: The high-toughness wear-resistant cable comprises a cable body and a protective layer arranged on the outer wall of the cable body, and the protective layer comprises the following components in parts by weight: Polypropylene 70-80 parts Modified ABS 12-16 parts Compatibilizer 10-13 parts Modified composite filler 9-10 parts 4-5 parts of additives; The compatibilizer is maleic anhydride grafted polypropylene; the auxiliary agent is a mixture of an antioxidant, a lubricant and an ultraviolet absorber in a mass ratio of 2.0-2.5:3.0-3.8:1.8-2.2; The preparation method of the modified ABS comprises the following steps: ABS, a reaction monomer and an initiator are mixed and kneaded, placed in a twin-screw extruder for melt extrusion, and pelletized to obtain modified ABS; the temperature of the melt extrusion is 170-180°C; the mass ratio of the ABS, the reaction monomer and the initiator is 14-16:1.5-1.8:0.10-0.12; the reaction monomer is a mixture of a carboxylic acid monomer and styrene in a mass ratio of 4-5:1.0-1.3; the carboxylic acid monomer is oleic acid; and the initiator is an initiator DCP; The preparation method of the modified composite filler comprises the following steps: Step 1: After mixing zirconium oxychloride octahydrate and anhydrous ethanol, add pretreated carbon nanotubes for ultrasonic treatment, adjust the pH value, place in a reaction kettle for heat preservation, perform vacuum filtration, dry and calcine to obtain composite particles; Step 2: heating and stirring the composite particles, anhydrous ethanol and coupling agent, filtering out the filtrate, washing, and drying to obtain a preform; Step 3: Mix the preform, anhydrous ethanol, mixed monomer and initiator, stir at a constant temperature, filter out the filtrate, wash and dry to obtain a modified composite filler; the mixed monomer is prepared by mixing glycidyl methacrylate and eugenol in a mass ratio of 3.0-3.6:1.0-1.3; the mass ratio of the preform, anhydrous ethanol, mixed monomer and initiator is 24-26:80-90:8.0-9.4:0.18-0.22; the initiator is azobisisobutyronitrile.
2. A high-toughness wear-resistant cable according to claim 1, characterized in that: The lubricant is one or both of oxidized polyethylene wax and montan wax; the antioxidant is one or both of antioxidant 1010, antioxidant 1098, antioxidant 168 and antioxidant 1076; the ultraviolet absorber is one or both of UV-9 and BP-6.
3. A high-toughness wear-resistant cable according to claim 1, characterized in that: In step one, the stirring and mixing is stirring at a speed of 400-600r / min for 20-30min; the ultrasonic treatment is ultrasonication at a frequency of 300-400W for 10-20min; the heat preservation treatment is heat preservation at 120-150°C for 10-16h; the pH value is adjusted to 10-12 using sodium hydroxide; the drying is drying at 80°C to constant weight; and the calcination is calcination at 500-560°C in an argon atmosphere for 1-2h.
4. The high-toughness wear-resistant cable according to claim 1, characterized in that: In step 1, the mass ratio of zirconium oxychloride octahydrate, anhydrous ethanol and pretreated carbon nanotubes is 2-3:90-100:8-10.
5. The high-toughness wear-resistant cable according to claim 1, characterized in that: In step 2, the heating and stirring is stirring at a temperature of 60-70°C for 4-5h; the washing is washing three times with anhydrous ethanol; the drying is drying at a temperature of 80°C to constant weight; the mass ratio of the composite particles, anhydrous ethanol and coupling agent is 14-16:40-50:6.0-7.2; and the coupling agent is vinyltrimethoxysilane.
6. The high-toughness wear-resistant cable according to claim 1, characterized in that: In step three, the constant temperature stirring is stirring at a temperature of 70-75° C. for 6-7 hours; the washing is washing three times with anhydrous ethanol; and the drying is drying at a temperature of 80° C. to constant weight.
7. A method for preparing a high-toughness wear-resistant cable according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: weighing polypropylene, modified ABS, compatibilizer, modified composite filler and auxiliary agent by weight, kneading for 20-30 minutes at 150-160° C., placing in a twin-screw extruder, melting and extruding at 180-200° C., and wrapping on the outer wall of the cable body.
Citation Information
Patent Citations
Flame-retardant TPE cable insulation material or sheathing material with electromagnetic shielding function and preparation method of TPE cable insulation material or sheathing material
CN108410112A
High-strength armored electric power composite optical cable and preparation method thereof
CN118295091A